Knowledge And Awareness About HIV/AIDS Among Women of Reproductive Age in A District of Northern India - Arun Singh; Swati Khan; Varsha Chaudhary; Kusum Narula; Zeashan Haider Zaidi; Amiya Pandey (Medsci Publications, 2012)
Motivation: The awareness about infectious disease like HIV/AIDS can affect and even helps in reducing the prevalence, incidence and no. of cases of the disease in the communities. With this view a cross sectional study was conducted during 2 months from July to August 2010 among women of reproductive age group in the urban and rural areas of Bareilly District to study and to compare the level of awareness in two different areas of the district about HIV/AIDS. Methodology: The two stage cluster sampling technique was adopted. A structured questionnaire was used to interview 620 women of reproductive age i.e. 310 women from each areas by house to house surveys. Each woman was interviewed for her level of awareness about HIV/AIDS. Chi (x2) square test and Standard Normal Variate (SNV) Test for comparison of two groups (rural & urban) proportion was done; z and p were calculated. Results: 27.41% of rural and 80.32% of urban women was aware about HIV/AIDS. In rural areas, homosexual intercourse (74.11%) is one the most common mode of transmission followed by heterosexual intercourse (24.70%) and in urban areas heterosexual intercourse (79.12%) followed by needles/ blades/ skin puncture (73.09%). The commonest sources of information among women in rural areas were TV (41.17%) and Radio (32.94%). In urban areas TV (90.36%) was more common media. Recommendations: As the awareness in the area especially in the rural areas was very low therefore it should be raised. The source of information should also be strengthened.